2023
DOI: 10.1097/md.0000000000033069
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patients admitted to an inner-city intensive care unit across 3 COVID-19 waves

Abstract: To expand our limited knowledge of COVID-19-related outcomes in patients admitted to inner-city intensive care unit (ICU across multiple infection waves. This retrospective study compared patients admitted to the ICU in Bronx, NY, during 3 COVID-19 waves (March 2020 to February 2022). Outcomes included in hospital mortality, length of stay (LOS), use of mechanical ventilation, and discharge disposition. The study included 716 patients (343, 276, and 97 in the first, second, and third COVID-19 waves, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…A number of smaller studies confirmed the invariably high mortality across the subsequent waves [ 2 , 25 ]. A number of studies found favorable time trends to lower mortality rate among COVID-19 patients admitted at the ICU, but the data were restricted to the first wave [ 1 , 3 5 , 26 , 27 ] or the differences in mortality between the waves were not adjusted for important patient characteristics [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of smaller studies confirmed the invariably high mortality across the subsequent waves [ 2 , 25 ]. A number of studies found favorable time trends to lower mortality rate among COVID-19 patients admitted at the ICU, but the data were restricted to the first wave [ 1 , 3 5 , 26 , 27 ] or the differences in mortality between the waves were not adjusted for important patient characteristics [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%